AN ASSESSMENT ON RECENT ISSUES OF TURKISH EDUCATION SYSTEM - ilker KÖSTERELİOĞLU (Fırat University, 2019)
The issues on Turkish education system has been clearly defined by many researchers. It is expected that determining the perspective of teachers, as one of the most important componentns of Turkish education system, regarding faced issues in education system is very important for making educational policy. The aim of this study is to identify the recent issues on Turkish Education System from teachers’ point of views. For this aim, this study addressed the following research question: “ What are the most common-recent issues on Turkish Education System?”. İn order to answer this question, the researchers have collected data from 23 teachers who pursued their Master’s degree in the department of Classroom Teaching, Graduate School, Amasya University in 2013-2014 academic years. The data had been collected qualitatively. The collected data were anaylzed by employing descriptive and content analysis techniques. In this regard, the study is kind of general screening model. When the researchers analyzed the collected that, they came to the conclusion that issues on teachers’ professional development and in-service training and vocational guidance issue on education are the most common issues on Turkish Education System. İn addition, the participants in this study reported the following themes as the most debated matters on Turkish Education System; issues on training and selection of educational administrators, issues on pre-service training of teachers, issues on private school offering specialized courses, physical infrastructure and deficiencies on hardware facilities, issues on the effects of politics on educational policy and issues on teachers’ promotion in their career. The results of this study demonstrated the vital importance of finding potential solutions to the above mentioned issues by the Ministry of National Education for the future of Turkey.